2016
DOI: 10.2967/jnumed.115.169839
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging and Quantitation of EphA2 Expression in Xenograft Models with 89Zr-DS-8895a

Abstract: Subtype A2 of the erythropoietin-producing hepatocellular tyrosine kinase (EphA2) cell surface receptor is expressed in a range of epithelial cancers. This study evaluated the molecular imaging of EphA2 expression in vivo in mouse tumor models using SPECT/MR and PET/MR and a humanized anti-EphA2 antibody, DS-8895a. Methods: DS-8895a was labeled with 111 In, 125 I, and 89 Zr and assessed for radiochemical purity, immunoreactivity (Lindmo analysis), antigen-binding affinity (Scatchard analysis), and serum stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 26 publications
2
24
1
Order By: Relevance
“…The biodistribution study demonstrated high uptake of 89 Zr-Df-Bz-NCS-DS-5573a in tumors, with levels rising by day 3 and maintained to day 7. The stable in vivo properties of 89 Zr-Df-Bz-NCS-DS-5573a were comparable to previously reported IgG1 humanized antibodies 32 , 44 , 45 . Uptake of 89 Zr-Df-Bz-NCS-DS-5573a was higher in the spleen of SCID mice versus BALB/c nu / nu mice.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The biodistribution study demonstrated high uptake of 89 Zr-Df-Bz-NCS-DS-5573a in tumors, with levels rising by day 3 and maintained to day 7. The stable in vivo properties of 89 Zr-Df-Bz-NCS-DS-5573a were comparable to previously reported IgG1 humanized antibodies 32 , 44 , 45 . Uptake of 89 Zr-Df-Bz-NCS-DS-5573a was higher in the spleen of SCID mice versus BALB/c nu / nu mice.…”
Section: Discussionsupporting
confidence: 86%
“…As shown by Sharma et al, the interaction between Fc gamma receptors (FγcRs) expressed by immune effector cells of myeloid origin (such as monocytes/macrophages prevalent in the spleen and a subset of dendritic cells and neutrophils in the bone marrow) and the Fc portion of antibodies results in anomalous biodistribution of radioimmunoconjugates in non-target organs such as the spleen of mice that have a highly immunodeficient background. Furthermore, the glycosylation status of the DS-5573a, an afucosylated human IgG1 antibody with increased binding affinity for FcγRIIIa, could have contributed to the non-target uptake of 89 Zr-DS-5573a in organs such as bone and spleen when compared to previously reported 89 Zr-labeled humanized IgG1 antibodies 32 , 35 , 44 , 45 .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…As a member of RTK family, it is well known that EphA2 is an emerging target for cancer therapeutics, due to its increased expression in tumor tissues [ 12 14 ]. Downregulation of EphA2 expression through various approaches inhibits malignant behavior in vitro and in vivo [ 31 33 ]. To date, the knowledge of functional roles and regulatory mechanism of EphA2 in GC are remains unclear due to the lack of applicable and practicable method to target it.…”
Section: Discussionmentioning
confidence: 99%
“…1C1 was also labeled with 64 Cu, after conjugation of the antibody with the chelating agent DOTA, and used for noninvasive PET of EphA2 levels in different tumor types (21). Recently, DS-8895a, an anti-EphA2 antibody, was labeled with appropriate radionuclides for PET and SPECT and applied to quantitative assessment of EphA2 expression and saturation in tumor models (22).…”
mentioning
confidence: 99%